From Margins to Mainstream: Uncovering Urban Informality of Street Vending in Kirtipur - Resham Thapa-Parajuli,; Bhuban Chandra Joshi,; Maya Timsina,; Bibek Pokharel, (Journal of Development and Administrative Studies, 2024)
Street vending is crucial in fostering economic growth and providing livelihood opportunities, particularly for urban migrants with limited formal employment prospects. This study examines the drivers, financial performance, and challenges street vendors face in Kirtipur municipality, Nepal. Findings reveal that street vending is primarily driven by necessity, with 53.33% of respondents citing the inability to secure formal sector jobs and 51.67% pointing to a lack of alternative skills. Respondents reveal that the sector is profitable, with 98.33% of vendors reporting profits and 55% achieving monthly savings between NPR 15,000 and NPR 30,000. Despite financial literacy and access to banking for 75% of respondents, initial investments predominantly came from informal sources, reflecting limited access to formal credit. Key challenges include weather conditions (80%), municipal interventions (65%), and inadequate infrastructure, such as drinking water (48.33%) and sanitation facilities (41.67%). The study highlights the need for local governments to implement skill development programs, formalize the sector, and invest in infrastructure to enhance the sector’s viability. Inclusive policies and financial support mechanisms are essential to mitigate risks and foster sustainability. Future research could adopt longitudinal methods or broader coverage to provide deeper insights into the dynamics of street vending across diverse contexts.